Health-Related Fitness Evaluation in First Grade Children & Guidelines for improvement through Aerobic Dance - Bousiou Σταυρούλα; Derri Βασιλική; Roka Στέλλα (Inquiries in Physical Education and Sport, 2004)
The purpose of this study was twofold: a) to present a way of health-related fitness assessment in first grade children, and b) to provide guidelines to enhance it through aerobic dance. The health-related Prudential Fitnessgram test battery (Cooper Institute, 1992) is proposed for the assessment of health-related fitness in young children. The tests are related to cardiorespiratory endurance, upper body and abdominal strength and endurance, hamstring and trunk flexibility, and body composition. For the attainment of the second purpose of this study, instruction ideas and methods for aerobic dance are presented which in their simplest form could be applied in first grade children to enhance their health-related fitness and enjoyment.